2017
DOI: 10.26633/rpsp.2017.156
|View full text |Cite
|
Sign up to set email alerts
|

Using evidence-informed policies to tackle overweight and obesity in Chile

Abstract: J, et al. Using evidenceinformed policies to tackle overweight and obesity in Chile. Rev Panam Salud Publica. 2017;41:e156. doi: 10.26633/RPSP.2017.156 An increasing number of studies from countries around the globe have described a cumulative proportion of the population suffering from overweight or obesity. The World Health Organization (WHO) has warned that in 2008, this epidemic reached catastrophic levels, affecting at least 35% of adults 20+ years of age and causing over 2.8 million premature deaths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
0
18
1
7
Order By: Relevance
“…In 2016, a labelling system using black octagons on packaging was introduced for food and beverages that are high in sugar, calories, sodium and saturated fats. In addition, foods and beverages with such labels have been banned from schools, while marketing of these products to children under the age of 14 years is no longer allowed [80, 81]. Initial results suggest a positive impact on knowledge and awareness, reductions in consumption of unhealthy foods and a positive response from the food industry.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a labelling system using black octagons on packaging was introduced for food and beverages that are high in sugar, calories, sodium and saturated fats. In addition, foods and beverages with such labels have been banned from schools, while marketing of these products to children under the age of 14 years is no longer allowed [80, 81]. Initial results suggest a positive impact on knowledge and awareness, reductions in consumption of unhealthy foods and a positive response from the food industry.…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, conversely, after a relatively small SSB tax increase from 13 to 18% in beverages with ≥ 6.25 g sugar/100 ml, two evaluations reported that the largest declines in taxed beverage purchase volumes were in high SEP groups [ 10 , 11 ]. This could have been due to non-tax factors such as media coverage of the tax or other policies such as front of pack labelling [ 12 ] having more impact on better educated consumers [ 13 ]. In Catalonia, Spain, a €0.12/L SSB tax on beverages with > 8 g sugar/100 ml, was associated with greater declines in high-income regions [ 14 ], and high-income households in a second study [ 15 ], who had greater reductions in soft drink expenditure shares and grams of sugar from soft drinks [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few countries have implemented statutory child-directed food marketing restrictions, and few studies have assessed those policies [31,32]. Guided by international recommendations to encourage diets that limit a person’s intake of saturated fats, free sugars, and sodium [33], Chile implemented the Food Labeling and Advertising Regulation (Law 20.606) [34,35,36] aimed at preventing childhood obesity through a labeling and marketing restriction on foods above certain defined thresholds in energy, saturated fats, sugars, and sodium [31,37]. The Chilean law, implemented in June 2016, has been considered the most comprehensive regulation of its kind to date [35], due to its wide scope of restrictions on food marketing and its criteria for qualifying foods as “high-in” the above nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…“High-in” products also cannot be promoted or sold within schools and are restricted from marketing to children <14 years of age. Products that are not classified as “high-in” are exempted from these restrictions [35,36]. The listed cut-off values only apply to products that contain an ingredient (e.g., added sugar) that increases the content of one or more of the critical nutrients beyond the specified thresholds.…”
Section: Introductionmentioning
confidence: 99%